Postoperative Airway Complications following Thyroid Surgery - Muhammad Hadi Khan, Ahmed Bin Zaheer, Varda Balouch, Muhammad Aslam, Gohar Latif, Dur I Shahwar (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Thyroid surgery is often done for thyroid diseases, such as benign and cancerous thyroid conditions. It is usually safe but if not diagnosed and treated promptly, the postoperative airway complications can be life-threatening. Airway compromise can occur following thyroid surgery as a result of a neck hematoma, laryngeal oedema, recurrent laryngeal nerve palsy, bilateral vocal cord palsy, or tracheomalacia. Identification of high risk patients is important as this will help to avoid morbidity and postoperative complications. Objective: To determine the frequency, types, associated factors, and outcomes of postoperative airway complications among patients undergoing thyroid surgery. Methods: This descriptive cross-sectional study was conducted at Tertiary Care Hospital in Rawalpindi, from January 2022 to January 2023. The patients were obtained by non-probability consecutive sampling and form a total of 72 patients who are having thyroid surgery. Patients were included who had undergone hemithyroidectomy, subtotal thyroidectomy, total thyroidectomy, or completion thyroidectomy at any age 18 years or older. A proforma was used to record the data related to demographic, clinical diagnosis, pre-operative airway findings, surgery type, intra-operative data, post-operative airway complications, management and outcomes. The data were analyzed by SPSS version 25. Frequencies were computed for categorical variables and the means and standard deviations were computed for continuous variables. A p value < 0.05 was deemed to be significant. Results: The mean age of patients was 42.6 ± 12.4 years. Females were more commonly affected, accounting for 53 (73.6%) cases. Multinodular goiter was the most frequent diagnosis, observed in 34 (47.2%) patients, and total thyroidectomy was the most commonly performed procedure. Postoperative airway complications were observed in 11 (15.3%) patients. Recurrent laryngeal nerve palsy was the most common complication, seen in 4 (5.6%) patients, followed by neck hematoma in 3 (4.2%), laryngeal edema in 2 (2.8%), tracheomalacia in 1 (1.4%), and bilateral vocal cord palsy in 1 (1.4%) patient. Airway complications were significantly associated with thyroid size greater than 5 cm, retrosternal extension, tracheal compression, difficult intubation, and longer operative duration. Conclusion: Postoperative airway complications occurred in a considerable proportion of patients undergoing thyroid surgery. Large goiter, retrosternal extension, tracheal compression, difficult intubation, and prolonged surgery were important risk factors. Careful preoperative airway assessment, meticulous surgical technique, secure hemostasis, and close postoperative monitoring are essential to prevent serious airway-related morbidity after thyroid surgery. Keywords: Thyroidectomy, airway complications, recurrent laryngeal nerve palsy, neck hematoma, tracheomalacia, postoperative complications.